Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00702-015-1442-0
|View full text |Cite
|
Sign up to set email alerts
|

Small intestine dysfunction in Parkinson’s disease

Abstract: The aim of this study was to assess the small bowel transit time in patients with Parkinson’s disease (PD). Ten patients with PD with no gastrointestinal complaints and ten healthy control subjects were investigated using single photon emission computed tomography fused with computed tomography after swallowing of a specially prepared capsule containing technetium 99m, which allowed visualization of the passage in the intestines. Preliminary results show that the small intestine passage in PD patients was prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
0
20
0
3
Order By: Relevance
“…78,79 Constipation occurs mainly due to delayed intestinal transit time and its effects are displayed in the small intestine and colon. 78,79 It is believed that constipation appears as a prodromal symptom years before the motor symptoms appear.…”
Section: Constipationmentioning
confidence: 99%
See 1 more Smart Citation
“…78,79 Constipation occurs mainly due to delayed intestinal transit time and its effects are displayed in the small intestine and colon. 78,79 It is believed that constipation appears as a prodromal symptom years before the motor symptoms appear.…”
Section: Constipationmentioning
confidence: 99%
“…78,79 Constipation occurs mainly due to delayed intestinal transit time and its effects are displayed in the small intestine and colon. 78,79 It is believed that constipation appears as a prodromal symptom years before the motor symptoms appear. 80 It has been reported that men, in their middle age, with less than one bowel movement per day had 4 times the risk of PD diagnosis for the next 20-25 years compared to men who had normal bowel movements.…”
Section: Constipationmentioning
confidence: 99%
“…Intestinal symptoms observed in PD are consistent with conditions of inflammation. Constipation in PD patients is attributed to slow intestinal transit time, a symptom that is also frequently observed in other conditions involving chronic GI inflammation such as inflammatory bowel disease (IBD) and obesity . Mechanistically, this condition has been linked to intestinal immune activation and to intestinal dysbiosis, which is another hallmark of disorders involving gut inflammation .…”
mentioning
confidence: 99%
“…Studies on asymptomatic ileostomy subjects established that the core ileal microbiota consists of (facultative) anaerobes including species from Clostridium Cluster I (Booijink et al, 2010;Zoetendal et al, 2012). Moreover, the transit time in the SI has been shown to be significantly longer in PD patients compared to healthy controls (with a median increase of 1.75 hours in PD patients) (Dutkiewicz et al, 2015;Knudsen et al, 2017). To this end, we tested whether DHPPA (100 µM) could affect the muscle contractility in the ileum.…”
Section: -(34-dihydroxyphenyl)propionic Acid Elicits An Inhibitory mentioning
confidence: 99%
“…Importantly, chronic idiopathic constipation is associated with SI motor abnormalities in the esophagus, stomach, jejunum and ileum (Panagamuwa et al, 1994;Van Der Sijp et al, 1993) and patients with constipation have a longer SI transit time compared to controls (Van Der Sijp et al, 1993). Only recently, SI dysfunction in PD was studied showing that the transit time in the SI was significantly longer in PD patients compared to healthy controls (HC) (Dutkiewicz et al, 2015;Knudsen et al, 2017). Using wireless electromagnetic capsules, the SI transit time was reported to be significantly higher in PD patients (400 min; n=22) compared to HC (295 min, n=15) (Knudsen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%